(untitled) (Biological Sciences - PJSIR, 2005)
The aim of this study was to prove some common fixed point theorems in fuzzy 2-metric spaces by removing the assumption of continuity, relaxing the compatibility or compatibility of type (a) or compatibility of type (b) to weak compatibility, and replacing the completeness of the space with a set of alternative conditions